2020
DOI: 10.1152/ajpcell.00510.2018
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MALAT1 promotes angiogenesis and immunosuppressive properties of HCC cells by sponging miR-140

Abstract: Hepatocellular carcinoma (HCC) is the most prevalent primary liver cancer in adults. Previous studies in our laboratory found that long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) was upregulated in HCC cells, which could affect the metastasis and invasion of HCC. However, the underlying mechanism remains unknown. Herein, we studied the interaction between MALAT1 and miR-140 on the regulation of angiogenesis and immunosuppressive properties. We revealed that the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 52 publications
2
79
0
Order By: Relevance
“…In particular, as we described, Huang et al reported that MALAT1 enhanced thyroid cancer angiogenesis by regulating FGF2 secretion of TAMs [63]. In HCC cells, MALAT1 could promote angiogenesis and regulate polarization of macrophages through sponging miR-140 [74]. These suggested that macrophages might be an important modulator of angiogenesis in the mechanisms of MALAT1.…”
Section: Involvement Of Lncrnas In Thesupporting
confidence: 53%
See 1 more Smart Citation
“…In particular, as we described, Huang et al reported that MALAT1 enhanced thyroid cancer angiogenesis by regulating FGF2 secretion of TAMs [63]. In HCC cells, MALAT1 could promote angiogenesis and regulate polarization of macrophages through sponging miR-140 [74]. These suggested that macrophages might be an important modulator of angiogenesis in the mechanisms of MALAT1.…”
Section: Involvement Of Lncrnas In Thesupporting
confidence: 53%
“…Many studies revealed the involvement of lncRNAs in the recruitment of macrophages to tumor cells and M1/M2 polarization of macrophages to change the tumor microenvironment. As we discussed before, MALAT1 not only acted as a potential cancer biomarker [54] but also regulated angiogenesis in diabetic retinopathy [71], tumor [63,[72][73][74], hindlimb ischemia [75], and brain vascular endothelium [76]. In particular, as we described, Huang et al reported that MALAT1 enhanced thyroid cancer angiogenesis by regulating FGF2 secretion of TAMs [63].…”
Section: Involvement Of Lncrnas In Thementioning
confidence: 63%
“…In particular, the levels of the lncRNA MALAT1 are increased in serum EVs from patients with CCA compared to PSC, displaying an AUC value of 1.00. In this regard, MALAT1 was found upregulated in HCC, contributing to tumor development and progression [81][82][83][84], as well as identified in HCC-derived exosomes [85]. MALAT1 is also increased in colon cancer cells, directly binding to miR-663a, thus acting as a competing endogenous lncRNA; as a result, important cancer-related miR-663a targets (TGFB1, PIK3CD, P21, JunB, and JunD) were affected [86].…”
Section: Discussionmentioning
confidence: 96%
“…33 MALAT-1 was shown to enhance the expression of vascular endothelial growth factor (VEGF)-A by sponging the miRNA miR-140, thereby promoting angiogenesis and accelerating HCC progression and metastasis. 34 MALAT-1 also increased the expression of Snail family zinc finger (Slug) by binding to miR-124-3p; Slug inhibited the expression of the epithelial marker cadherin 1, 35 thereby stimulating HCC cell migration and metastasis. 36 Upregulated MALAT-1 can sponge miR-30a-5p, leading to increased expression of the mesenchymal marker vimentin; EMT is consequently induced through the migration and invasion of HCC cells.…”
Section: Malat-1 In Cancer Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%